ANALISIS PENDAPATAN BUMDes USAHA KOMPOS DI KECAMATAN TEBING TINGGI KABUPATEN TANJUNG JABUNG BARAT - Salma Hasanatus Sholeha; Firmansyah; Indra Sulaksana (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the income of Village-Owned Enterprises (BUMDes) engaged in compost production in Tebing Tinggi District, Tanjung Jabung Barat Regency. The four BUMDes selected as research objects are Karya Bersama, Sumber Rezeki, Gerbang Nusantara, and Mandiri Sejahtera. The research method used is a survey method with a purposive sampling technique, while the data were collected through interviews, questionnaires, and secondary documents obtained from relevant institutions. Data analysis was conducted using a financial approach, including the calculation of revenue, total costs, and business income. The results of the study show that compost production managed by BUMDes contributes positively to increasing village income. Karya Bersama BUMDes achieved the highest income, supported by a larger investment capital, adequate production facilities, and higher production capacity. Meanwhile, Sumber Rezeki, Gerbang Nusantara, and Mandiri Sejahtera BUMDes generated lower income due to limited production facilities and high operational costs. The main factors influencing the income of compost businesses include production volume, cost efficiency, availability of raw materials, and business management strategies. The study concludes that compost businesses managed by BUMDes in Tebing Tinggi District are feasible to be developed as one of the main sources of village income. Strengthening investment, increasing production capacity, and implementing more professional management are recommended to improve the performance of compost enterprises in the future.